THE EFFECTIVENESS INTERACTIVE LEARNING TO IMPROVE STUDENT`S WRITING DESCRIPTIVE TEXT SKILL FOR CLASS X.2 SMA NEGERI 1 MEMBALONG ACADEMIC YEAR 2014/2015 - Nanang Narwianta (Sirok Bastra, 2015)
This classroom action research has conduct to improve the learning process that optimum yet. The objective of this research is to know the effectiveness of interactive learning to improve the writing descriptive text skill for students class X.2 in SMA Negeri 1 Membalong. This research has been conduct in 2 cycles, each cycle consist of 2 meetings. Cycle 1 is held on February 16 and 17, 2015. Cycle 2 is held on February 23 and 24, 2015. In the beginning of this study, in learning is low. Based on the reflection in cycle 1 and cycle 2 it shows that interactive learning through group discussion strategy is not maximal to improve the students participation, student being active and enthusiastic on learning process but interactive learning with game strategy (group to group exchange) the students active on learning process reach 80%, students participation and enthusiastic is 93,33% and the students writing descriptive text skill can be optimalize so the student`s learning outcomes is 77,78%. It can be conclude that interactive learning can improve the students writing descriptive text skill for students class X.2 SMA Negeri 1 Membalong.